Single-plate Swipe Couplings On Four-wheeled Vehicles - Rasyid, Kurniadi; Pambudi, Tutur Angger (Pandawan, 2020)
The clutch is an absolutely necessary part of the gasoline cars and the other types where the main drive is obtained from the fuel in the cylinder. The author starts planning this friction coupling with the theory and shifting system of style, then determines the type of clutch plate to be worn, determining the large diameter of the clutch shaft, specifies the thick of the friction plate, the spring reducer, the flywheel connecting Bolt with the flux, the flywheel connecting bolt with the engine shaft, the rivet connector of the friction plate with the spring disc, the rivet of the disc-connector with the sub plate, the rivet of the sub-plate and the spline hub, the rivet of the Cover flux, clutch shaft bearings, bearing holders, as well as heat calculations and age of friction plates. Specifies the type of clutch plate to be worn, determining the large diameter of the clutch shaft, determining the thick of the friction plate, the damper spring, the flywheel connecting Bolt with the flux, flywheel connecting bolt with engine shaft, rivet swipes with friction plate with disc spring, Rivet Connector Spring with sub plate, rivet sub plate rivets with spline hub, rivet fastening rivets with flux cover, clutch shaft bearings, bearing holders, as well as heat calculation and age of friction plates. Single-plate swipes are designed so that they can transmit power/rotation in a rotating or unrotating state. The type of coupling discussed here is the fixed clutch that uses a plate that serves as a medium of friction between the flywheel and the pressing plate. The purpose of writing these planning tasks to meet and complement the course of the machine element, the authors try to plan and discuss the clutch system